DNA Methylation and Histone Acetylation Contribute to the Maintenance of LTP in the Withdrawal Behavior Interneurons in Terrestrial Snails - Alena Zuzina; Daria Kolotova; Pavel Balaban (Cells)
Accumulated data indicate that epigenetic regulations, including histone modifications and DNA methylation, are important means for adjusting the expression of genes in response to various stimuli. In contrast to the success in studying the role of DNA methylation in laboratory rodents, the role of DNA methylation in the terrestrial snail Helix lucorum has been studied only in behavioral experiments. This prompted us to further investigate the role of DNA methylation and the interaction between DNA methylation and histone acetylation in the mechanisms of neuroplasticity in terrestrial snails using in vitro experiments. Dysregulation of DNA methylation by the DNMT inhibitor RG108 significantly suppressed the long-term potentiation (LTP) of synaptic inputs in identified neurons. We then tested whether the RG108-induced weakening of potentiation can be reversed under co-application of histone deacetylase inhibitors sodium butyrate or trichostatin A. It was found that increased histone acetylation significantly compensated for RG108-induced LTP deficiency. These data bring important insights into the functional role of DNA methylation as an important regulatory mechanism and a necessary condition for the development and maintenance of long-term synaptic changes in withdrawal interneurons of terrestrial snails. Moreover, these results support the idea of the interaction of DNA methylation and histone acetylation in the epigenetic regulation of synaptic plasticity.